A mechanical perspective on phagocytic cup formation. (October 2020) - Vorselen, Daan; Labitigan, Ramon Lorenzo D.; Theriot, Julie A.
Abstract: Phagocytosis is a widespread and evolutionarily conserved process with diverse biological functions, ranging from engulfment of invading microbes during infection to clearance of apoptotic debris in tissue homeostasis. Along with differences in biochemical composition, phagocytic targets greatly differ in physical attributes, such as size, shape, and rigidity, which are now recognized as important regulators of this process. Force exertion at the cell–target interface and cellular mechanical changes during phagocytosis are emerging as crucial factors underlying sensing of such target properties. With technological developments, mechanical aspects of phagocytosis are increasingly accessible experimentally, revealing remarkable organizational complexity of force exertion. An increasingly high-resolution picture is emerging of how target physical cues and cellular mechanical properties jointly govern important steps throughout phagocytic engulfment. Highlights: Cytoskeletal forces, cytoplasmic viscosity, membrane tension, and cortical tension are key regulators of phagocytosis. Cellular force exertion during phagocytosis shows complex spatiotemporal patterns, inconsistent with a simple zipper model. Phagocytic targets widely differ in their rigidity, which is a crucial regulator of phagocytosis in the 0.1-100 kPa range. Target geometry is a complex parameter, wihch can regulate phagocytosis through local and global shape cues.